Climate dialogues and adaptive management: interventions for an experiential learning space in Novo Airão (AM), Amazon Region - Oliveira, Lyvia Amado de; Toledo, Renata Ferraz de; Santos Junior, Marcelo Augusto dos; Moretto, Evandro Mateus (Sustainability in Debate, 2025)
Climate change intensifies extreme events in the Amazon Region, including droughts and floods, which affect its local socio-ecological systems and increase local challenges and uncertainties. Experiential learning is an assumption in adaptive management that seeks to address information gaps and contribute to adjustments in the management process in response to uncertainties, increasing the adaptive capacity of socio-ecological systems. This paper presents the results of an action research study that aimed to promote reflexive thinking and understand the experiential learning process under the climate challenges in the Amazon Region. The study conducted participatory workshops with public administration actors, private sector actors, scholars, and civil society in the municipality of Novo Airão, located in the Amazonas state (AM). We employed dialogical approaches and knowledge-building during the participatory workshops, integrating local, technical, and scientific knowledge. The oriented interaction among actors and the use of these methodological tools allowed us to identify risk areas and vulnerabilities and propose actions from a local perspective. This process indicated that spaces for dialogue strengthen the development of contextualised responses, and it highlights adaptive management as a strategy for addressing climate uncertainties.